Cisgender Women and Transgender People in Prison: A Critical Perspective on the Penal System (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2026)
In this article, through a characterization of the population of (cis) women and transgender people incarcerated in Argentina, we seek to account for how the power to punish is exerted upon these populations within the framework of the so-called "punitive turn". We will present the results of a qualitative investigation based on the cross-referencing of data and information from secondary sources. Furthermore, we propose the hypothesis that feminist movements, through their punitivist expressions, may contribute to the intensification of the penal system, with pernicious repercussions for the women and trans people reached by this system. We consider that the proposed analysis can contribute to the debate regarding the limits, complexities, and consequences of appealing to the penal system as a way to manage conflicts
Keywords: Prison, Gender, Penal System, Punitivism